2016
DOI: 10.1016/j.vetpar.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii in stranded marine mammals from the North Sea and Eastern Atlantic Ocean: Findings and diagnostic difficulties

Abstract: a b s t r a c tThe occurrence of the zoonotic protozoan parasite Toxoplasma gondii in marine mammals remains a poorly understood phenomenon. In this study, samples from 589 marine mammal species and 34 European otters (Lutra lutra), stranded on the coasts of Scotland, Belgium, France, The Netherlands and Germany, were tested for the presence of T. gondii. Brain samples were analysed by polymerase chain reaction (PCR) for detection of parasite DNA. Blood and muscle fluid samples were tested for specific antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Kirkwood et al [15] observed brain lesions in 2% of the animals and Jauniaux et al [14] reported brain lesions in 4% of the animals. In previous studies, carcinoma [42], Toxoplasma [43, 44], and A. fumigatus [32] have been diagnosed as causes of brain lesions. In comparison, we observed A. fumigatus or Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Kirkwood et al [15] observed brain lesions in 2% of the animals and Jauniaux et al [14] reported brain lesions in 4% of the animals. In previous studies, carcinoma [42], Toxoplasma [43, 44], and A. fumigatus [32] have been diagnosed as causes of brain lesions. In comparison, we observed A. fumigatus or Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Also, because gulls live in close proximity to human populations, they have access to refuse tips (Ceia et al, 2014; Navarro et al, 2016; Ramos et al, 2009; Real et al, 2017; Steigerwald et al, 2015). Recently, it has also been suggested that marine prey, and filter feeders in particular, may accumulate oocysts (Massie et al, 2010), explaining therefore the ubiquity of this parasite in the marine environment (Dubey et al, 2005; Honnold et al, 2005; van de Velde et al, 2016; Verma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in this study the seroprevalence of T. gondii was higher in striped dolphins (33.33%, 5/15), a pelagic species, than in bottlenose dolphins (10.00%, 1/10). Differences between serological and PCR results can be explained by the heterogeneous distribution of T. gondii and parasite absence in the low amount of nervous tissue (few mgs) used for molecular analysis, especially in the case of low infection intensity [ 50 ]. It is interesting to note that the only subject found PCR positive in this study showed the highest serological titre.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the only subject found PCR positive in this study showed the highest serological titre. Nevertheless, PCR negativity to T. gondii of nervous tissues from serologically positive dolphins has been previously reported [ 19 , 50 ]. Furthermore, it is also possible that the positivity observed in some animals in this study was due to infections caused by other protozoa antigenically related to T. gondii and reported in dolphins, such as Neospora caninum and Sarcocystis spp.…”
Section: Resultsmentioning
confidence: 99%